2016
DOI: 10.7150/ijbs.15992
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 Protects against Oxidative Stress-induced Neuronal Apoptosis through Myosin IIA-actin Related Cytoskeletal Reorganization

Abstract: Oxidative stress-induced cytoskeletal dysfunction of neurons has been implicated as a crucial cause of cell apoptosis or death in the central nervous system (CNS) diseases, such as neurodegenerative and psychiatric diseases. The application of neuroprotectants rescuing the neurons from cytoskeletal damage and apoptosis can be a potential treatment for these CNS diseases. Ginsenoside Rg1 (Rg1), one of the major active components of ginseng, has been reported possessing notable neuroprotective activities. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 68 publications
0
33
1
Order By: Relevance
“…Primary cultures of cortical neurons were prepared from embryonic day 16–18 Sprague-Dawley rats according to previously described methods [ 42 ]. Briefly, the cerebral cortices were dissected out and the meninges were carefully removed under a microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Primary cultures of cortical neurons were prepared from embryonic day 16–18 Sprague-Dawley rats according to previously described methods [ 42 ]. Briefly, the cerebral cortices were dissected out and the meninges were carefully removed under a microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Hemodynamics and pulmonary circulation parameters, such as cardiac index, intracavitary blood volume, and central venous pressure, significantly improved (Sun et al, 2015 ). In addition, a wide range of pharmacological activities have been reported for ginsenosides, including anti-aging (Hu et al, 2015 ), immunoregulation (Yang et al, 2017 ), neuroregulation (Wang et al, 2016b ), lipid regulation (Huang et al, 2017b ), antithrombosis (Ban et al, 2017 ), and wound healing (Li et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…37 Moreover, caspase-3/ROCK1/MLC has also been proved to be a novel cyclic positive feedback loop for regulating apoptosis in different cell types, such as cardiac myocyte, human leukemia cells and neurons. [40][41][42] We have previously reported the caspase-3/ROCK1/MLC feedback loop in H 2 O 2induced PC12 cell injury, and NMMHC IIA is also involved in a positive feedback loop that links caspase-3/ROCK1/MLC signaling axis. 13,22 Our present findings confirmed that I/ R-induced caspase-3 cleavage led to decrease of ROCK1 and MLC phosphorylation.…”
Section: Discussionmentioning
confidence: 99%